The systematic component of monetary policy in SVARs: An agnostic identification procedure - Jonas E. Arias; Dario Caldara; Juan Francisco Rubio-Ramírez (Federal Reserve Bank of Atlanta, 2016)
This paper studies the effects of monetary policy shocks using structural vector autoregressions (SVARs). We achieve identification by imposing sign and zero restrictions on the systematic component of monetary policy. We consistently find that an increase in the fed funds rate induces a contraction in output. We also show that the identification strategy in Uhlig (2005), which imposes sign restrictions on the impulse responses to a monetary shock, does not satisfy our restrictions on the systematic component of monetary policy with high posterior probability. This finding accounts for the difference in results with Uhlig (2005), who found that contractionary monetary policy shocks have no clear effect on output. When we reconcile the two approaches by combining both sets of restrictions, monetary policy shocks remain contractionary.
Keywords: E52; C51; 330; SVARs; monetary policy shocks; systematic component of monetary policy